Research on ecotoxicology of microplastics on freshwater aquatic organisms. Issue 1 (1st January 2019) - ma, Piao; Wei Wang, mu; Liu, Hui; Feng Chen, yu; Xia, Jihong
ABSTRACT: As a new type of pollutant, microplastics are an emerging scientific and social concern in the environment and are widely distributed in the aquatic environment and organism. Nowadays, researches on microplastic pollution mainly focus on the marine environment. As a bridge for the migration of microplastics from the terrestrial environment to the marine environment, the freshwater environment has been deserved more attention. Published articles on microplastics in freshwater environments were reviewed in this paper, and four typical behaviors of microplastics were summarized: biological ingestion, biological attachment, adsorption of pollutants and release of plasticizers. In addition, the progress in research and results on the ecological toxicity of microplastics to freshwater organisms was also analyzed. Finally, emphasis on future research on the toxicity of microplastics to freshwater aquatics organisms was made throughout this review as a tool in microplastic risk assessment research.